EVALUASI GENOTIPE TANAMAN KACANG HIJAU ( Vigna radiata L.) GENERASI M3 HASIL RADIASI SINAR GAMMADIBANDINGKAN DENGAN TETUA - Deliana, Deliana; Rasyad, Aslim (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
This studywas intended to determine variability of mungbean genotypes (Vigna radiata L.) at M3 generation after treated by gamma ray radiation. The field experiment has been carried out in the experimental station of the Faculty of Agriculture, University of Riau from January to March 2018.This research was conducted by a paired experimental in which two generations of mungbean such as M3 generation were compared to its parental population. The field  experimental was arranged in a completely randomized design with 5 replications. Seed of every population was planted in a plot of 3 m length and 2 m wide. Planting space were 30 cm x 20 cm so as to obtain 100 individual plants per plot. All plants in every  plot were observed based on the important agronomic traits, then  data were tabulated  and calculated the value of variation in each population. The parameters observed were plant height, number of main steminternodes,  flowering and  harvest dates, number of pods per plant, number of seeds per plant, number of seeds per pod, weight of seeds per plant, and weight of 100 seeds. The results showed that gamma ray radiation increased the number of main stem internodes, seed  number per pod, and the weight of 100 seeds at M3generation compared to controls. All characters had high variability value in the M3 generation except the number of seeds per pod in whichM0variation was higher than M3. Keywords: mungbean, gamma ray, mutation, variation